2018
DOI: 10.1590/s2175-97902017000417006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, antibacterial potential and characterization of active fraction of Dioscorea pentaphylla L. tuber extract collected from Similipal Biosphere Reserve, Odisha, India

Abstract: Dioscorea pentaphylla L., a wild tuber is used both as food and medicines among different ethnic groups of Similipal Biosphere Reserve, India. Tubers are used against skin infections. In order to establish and confirm tribal claims, methanol extract was subjected to fractionation. The active fraction (DP1) was subsequently used for further purification and NMR (Nuclear magnetic resonance) characterization. The phytochemical analysis revealed the presence of saponin groups. The antibacterial activity of DP1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Using the agar well diffusion and pour plate method, the authors reported extracts of D. dumetorum and D. hirtiflora tubers as possible sources of antimicrobial agents with their antimicrobial efficacy directly linked to the phenolic contents of the plants and DPPH scavenging activity. Kumar et al [ 24 ] compared the antibacterial activity of D. pentaphylla tuber extracts and antibiotics (penicillin and kanamycin) on five selected bacterial strains ( Vibrio cholera , Shigella flexneri , Salmonella typhi , Streptococcus mutans and Streptococcus pyogenes ). Their findings revealed a significant inhibitory activity of D. pentaphylla tuber extracts against the tested bacteria.…”
Section: Therapeutic Potentials Of Yamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the agar well diffusion and pour plate method, the authors reported extracts of D. dumetorum and D. hirtiflora tubers as possible sources of antimicrobial agents with their antimicrobial efficacy directly linked to the phenolic contents of the plants and DPPH scavenging activity. Kumar et al [ 24 ] compared the antibacterial activity of D. pentaphylla tuber extracts and antibiotics (penicillin and kanamycin) on five selected bacterial strains ( Vibrio cholera , Shigella flexneri , Salmonella typhi , Streptococcus mutans and Streptococcus pyogenes ). Their findings revealed a significant inhibitory activity of D. pentaphylla tuber extracts against the tested bacteria.…”
Section: Therapeutic Potentials Of Yamsmentioning
confidence: 99%
“…These authors reported the therapeutic potentials of peptides and proteins isolated from several species of yams including D. alata , D. cayenensis , D. japonica , D. pseudojaponica and D. polystachya (formerly known as D. opposita or D. batatas ), as well as the possible clinical applications for the treatment of inflammatory diseases, cardiovascular diseases, aging disorders, menopause, cancers and osteoporosis. Furthermore, the use of different species of Dioscorea for birth control and skin infections has been reported [ 23 , 24 ]. Nashriyah et al [ 25 ] reported the use of D. hispida in cosmetics for pigmentation remedy.…”
Section: Introductionmentioning
confidence: 99%
“…differ [ 32 ]. A study on the Dioscorea species of India attempted to screen the ethnobotanical importance of root tubers and proposed that differences exist within species in terms of phytochemicals and their concentrations [ 33 , 34 , 35 ]. The secondary metabolite profiling of the Dioscorea alata L. also helped to clarify the traditional selection process of the grater yam cultivars [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between reducing activity and the presence of mixed phenolic compounds was found to be positive and statistically significant (r= 0.94, P < 0.05). The maximum antioxidant potential of Anchote (92%) is greater than that of T. Purthenium (80%), A. Grandifolia (85%), A. Crithmifolia (88%), A. Absinthium (90%), L. Latifolium (89%), A.panicii (79%), A. Sylvestris (36%), H.officinalis (84%) [52], Baccopa monnieri (82%) [53], Withania somnifer Dunal (83%) [54], Tacca pinatifida (76.53%) [55], C. esculenta corm (19.35%) [56], Dioscorea pentaphylla L.(89.41%) [57] but lower than that of Centella asiatica (95.78%) [53]. This work reveales that Anchote has significant antioxidant activity due to the availability of different phytochemicals in it.…”
Section: Antioxidant Activity Testmentioning
confidence: 99%